Pregnancy-Associated Malaria in a Rural Community of Ghana - Ofori, M.E.; Ansah, E; Agyepong, I.; Ofori-Adjei, D.; Hviid, L.; Akanmori, B.D. (Ghana Medical Journal, 2009)
Objectives: Pregnant women in malaria-endemic communities are susceptible to Plasmodium falciparum infections, with adverse consequences including maternal anaemia, placental malaria parasitaemia and infant low birth weight (LBW). We sought to assess the prevalence, incidence, and clinical markers of pregnancy- associated malaria (PAM) in a rural district of Ghana. Methods: A total of 294 pregnant women were enrolled and followed passively and actively, monthly and weekly until delivery. Haemoglobin levels, malaria parasitaemia and Hb electrophoresis were done from peripheral blood samples. At delivery, placental smears were examined for malaria parasites. Results: Prevalence of peripheral blood P. falciparum parasitaemia at enrolment was 19.7% and related to parity. Incidence rate of parasitaemia was 0.06 infections/ person/month [95% confidence interval (CI): 0.04 to 0.08]. Symptomatic infections rose sharply from the first trimester to the last. Prevalence of malaria parasites in the placenta was 35.9% (61/170) and highest among primigravidae (P(2)=0.006). Incidence of LBW infants was 17.7% (30/170), most common among those with placental P. falciparum infection (P(2)=0.005) corresponding to a relative risk of 2.8 [1.4 to 5.2]. Median infant birth weight in those with placental infection was significantly lower than in those without infections (P(2)=0.001). Maternal haemoglobin levels were lower (9.7 [9.3-10.1] g/dL) at enrolment, among women who subsequently had placental P. falciparum infection than among those who did not have placental infection at delivery (10.5 [10.2- 10.8] g/dL) (P (t)=0.003). Conclusion: Primigravidae and secundigravidae are significantly at risk of developing PAM, and low haemoglobin during pregnancy is a clinical indicator of placental P. falciparum infection.
Journal Article
Keywords: Placenta; pregnancy; malaria; haemoglobin